Grain Sorghum Response to Irrigation in Virginia. Issue 1 (22nd November 2017) - Oakes, Joseph; Sadeghpour, Amir; Balota, Maria
Abstract : Core Ideas: Irrigating grain sorghum is not economical in Virginia. There was no hybrid response to irrigation. A substantial decrease in irrigation cost is necessary to make irrigating sorghum economical.